INHIBITION OF 3-HYDROXY-3-METHYLGLUTARYL-COENZYME A REDUCTASE ACTIVITY BY EXTRACTS OF GARCINIA XANTHOCHYMUS MESOCARP AND TOTAL FLAVONOID ASSAY QUANTIFICATION OF THE MOST ACTIVE EXTRACT - Megawati,; Elya, Berna; Puspitasari, Nuraini (International Journal of Applied Pharmaceutics, 2018)
Objective: This study aims to determine the inhibitory activity of Garcinia xanthochymus mesocarp extracts against 3-hydroxy-3-methylglutaryl -coenzyme A (HMG-CoA) reductase. Methods: G. xanthochymus mesocarp was macerated sequentially using n-hexane, ethyl acetate, and methanol. Phytochemical screening and quantification of total flavonoids were performed on the most active extract. Results: Based on the tests, n-hexane, ethyl acetate, and methanol extracts had inhibitory activities of 12.30±1.098%, 55.63±10.584%, and 44.01±1.053%, respectively. The results showed that the ethyl acetate is the most active extract, containing flavonoid, terpenoid, glycoside, and anthraquinone compounds. The amount of total flavonoid contained in ethyl acetate extract was 1.61% or 16.114 mg QE/g toward quercetin. Conclusion: The n-hexane, ethyl acetate, and methanol extracts of G. xanthochymus have inhibitory actions against HMG-CoA reductase activity in vitro. Further research is still needed to strengthen this finding.